Determination of Cancer Antigen CA15-3 and Carcino Embryonic Antigen CEA concentration as Tumor Markers in Patients with Stomach and Colorectal cancers. - AL-saady, Rana. K.; AL-Tai, Wafa. F.; Himdan, Taqi A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Tumor markers are often requested as part of a diagnostic workup, and increased concentrations in serum may suggest malignancy of a particular organ. However, definitive diagnosis is based on histological evaluation of the involved tissue.Objective: The aim of present study is to evaluated CEA and CA15-3 in order to clarify at least in part their possible use as an early diagnosis tools in sera of patients with stomach, colon and rectum cancers.Patients and methods: The study was carried out on 61 subjects comprising of 16 patients with colon cancer group (G1), 10 patients with rectum cancer group (G2), 10 patients with stomach cancer group (G3) and 25 normal healthy control The patients were selected, during the period from (February 2010 to January 2011) with age range of (40-55) years. The patients were admitted to Al khadmiya Teaching Hospital, Iraq for treatment. Serum CA15-3 and CEA were measured by enzyme linked immunosorbent assay (ELISA).Results: The serum value of CA15-3, was highly significant increase (p≤0.001) in G1 and G2 cancer groups compared to normal healthy subjects. while the serum value of CEA of G1 and G2 was a significant increase (p≤0.05)compared to control but CA15-3 and CEA in serum of G3 showed no significant difference(p>0.05) compared to control.Conclusions: In this study CA15-3 and CEA could not be of valuable use as diagnostic markers in serum of stomach cancer while in colon and rectal cancers are of useful value.